METHODS OF USING PHYSICAL-TECHNICAL DEVICES IN MEDICINE - Makhsudov, V.G. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
This article focuses on the physics-based techniques of physics, which focuses on ultrasonic, laser, and unique surgical equipment, electrical currents, optical instruments, ophthalmoscopes, endoscopes, computer-assisted magnetic resonances, magnetic resonances. and focuses on the main aspects of human health. The importance of physical devices in medicine